FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG DI BANK SYARIAH (STUDI KASUS DOSEN UNIVERSITAS SYIAH KUALA) - Siti Maisarah Amanda; M.Shabri Abd. Majid (FEB Universitas Syiah Kuala, 2019)
The objective of this research is to examine and analyze the influences of knowledge, income, locations, products, and services on the intention of the customers to saving in Islamic banks. The method used in this research was a quantitative one. The population of this research consists of lecturers of Syiah Kuala University. By using a stratified random sampling technique, 100 respondents were chosen. The data collected were then analyzed by using the multiple linear regression analysis and SPSS. The result indicates that the intention of saving at Islamic banks was influenced by knowledge, income, locations, products and services. Keywords: knowledge, income, location, products, services, intention, and Islamic bank AbstrakPenelitian ini bertujuan untuk menguji dan menganalisa pengaruh pengetahuan, pendapatan, lokasi, produk, dan pelayanan terhadap minat menabung di bank syariah. Metode penelitian yang digunakan adalah metode penelitian kuantitatif. Populasi dalam penelitian ini adalah dosen Universitas Syiah Kuala dengan teknik pengambilan sampel stratified random sampling dan diperoleh sampel penelitian 100 responden. Untuk metode anlisis data menggunakan metode analisis regresi linear berganda dengan SPSS. Hasil dari penelitian ini menunjukkan bahwa pengetahuan, pendapatan, lokasi, produk, dan pelayanan mempengaruhi minat menabung di bank syariah.